(untitled) (Fiep Bulletin - online, 2019)
Motor development, be in any sport, must be worked in stages and each stage, must stimulate in the student,pleasure, the interest and become significant in the sporting trajectory of the same. For a good development of the acceptanceand better learning of physical activities, there must be a program related with the individual’s interests who participate of theseactivities. So, this study had as aim to compare the motor aspects in children from 7 to 10 practicing years of the futsal in SantaInês – PB. It is about an experimental research, with quantitative approach. A test was applied to compare data about benefits ofthe futsal classrooms in the motor development. The balance tests were used, laterality and temporal space, as well asPsychomotor Evaluation Protocol was applied. For data analyses were used Software Excel and Statistical Package for theSocial Sciences (SPSS). Three tests were performed to evaluate motor skills of children in futsal. These tests were balance(90.0%) of children performed and (10.0%) didn’t, Laterality (95.0%) of children did and (5.0%) did not, and temporal space where (80.0%) of children did and (20.0%) did not. Concluded the present study, that practice of futsal in childhood brings severalbenefits to motor development of children in age group of 7 to 10 years, once all children had facilities to perform the tests.